2020
DOI: 10.1371/journal.pone.0242766
|View full text |Cite
|
Sign up to set email alerts
|

Stay with your community: Bridges between clusters trigger expansion of COVID-19

Abstract: In this study, the spread of virus infection was simulated using artificial human networks. Here, real-space urban life was modeled as a modified scale-free network with constraints. To date, the scale-free network has been adopted for modeling online communities in several studies. However, in the present study, it has been modified to represent the social behaviors of people where the generated communities are restricted and reflect spatiotemporal constraints in real life. Furthermore, the networks have been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Another reason for this discrepancy is the PEV for individuals ≥65 years of age, which was higher than that for individuals <65 years of age (see Figure 2 b). This different tendency can be hypothesized in terms of community [ 25 ]: the percentage of infected people ≥65 years would be lower due to a higher vaccination rate. Another potential bias is the population younger than 12 years, for whom the vaccination was not yet licensed.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for this discrepancy is the PEV for individuals ≥65 years of age, which was higher than that for individuals <65 years of age (see Figure 2 b). This different tendency can be hypothesized in terms of community [ 25 ]: the percentage of infected people ≥65 years would be lower due to a higher vaccination rate. Another potential bias is the population younger than 12 years, for whom the vaccination was not yet licensed.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [ 42 ], it has been modified to represent the social behaviors of people where the generated communities are restricted and reflect spatiotemporal constraints in real life. They concluded that the bridge between infected and fresh clusters may trigger new virus spread.…”
Section: Discussionmentioning
confidence: 99%
“…However, locations with high ρ values-places with few users but many contact objects-are where users share the same spaces (locations and vehicles) both directly and indirectly, which increases the chances of contact with an unspecified number of people. From the perspective of remaining within an inter-community to prevent infection spread (Ohsawa and Tsubokura, 2020), we should avoid these places and refrain from contacting the objects there.…”
Section: Locations/vehicles and Touched Objectsmentioning
confidence: 99%
“…Third, this study detailed measures to be taken at each location through a discussion about the risk of infection through inanimate surfaces based on the objects that participants came into contact with. As with studies on the simulation of infection control (Ohsawa and Tsubokura, 2020) or measurement of household water insecurity (Stoler et al, 2020), this study does not investigate infected individuals or SARS-CoV-2 RNA directly, but provides useful insights into COVID-19 control and prevention measures.…”
Section: Introductionmentioning
confidence: 99%